ASSESSMENT TECHNIQUES USED BY TEACHERS IN ASSESSING STUDENTS' SPEAKING SKILL : A Case Study of English Teachers in One Senior High School in Tasikmalaya - Ramadani, Zahara (2014)
This study discuses the assessment techniques used by teachers in assessing students' speaking skill. It aims to explore the various techniques in assessing students' speaking skill as well as teachers' reasons and difficulties in implementing those assessment tecnhiques. This is a case study conducted at one of senior high school in Tasikmalaya. The data collected through observation, interview, and documents analysis are analyzed qualitatively based on the form proposed by Brown (2004). The findings indicate that the assessment techniques used by teachers in assessing speaking skill are as follows: retelling, role play, picture-cued story telling, discussion, picture-cued task, read aloud, and games. Moreover, practicality, efficiency, and authenticity are the reasons behind the use of those speaking assessment techniques. Meanwhile, the difficulties in implementing those assessment tecniques are students' limited vocabulary, students' motivation, and students' willingness to speak. Based on the findings, it can be concluded that various speaking assessment tasks can be used in assessing students' speaking skill. Moreover, it is necessary for teachers to recognize their students' difficulties in order to use appropiate assessment techniques. Keywords: assessment techniques, speaking Penelitian ini membahas tentang teknik penilaian yang digunakan oleh guru dalam menilai kemampuan berbicara siswa. Hal ini dilakukan untuk mengetahui lebih jauh mengenai berbagai macam teknik dalam menilai kemampuan berbicara siswa beserta alasan-alasan guru dalam penggunaan teknik tersebut dan kesulitan dalam mengimplemntasikan teknik-teknik tersebut. Penelitian ini merupakan suatu studi kasus yang dilakukan di salah satu sekolah menengah atas di Tasikmalaya. Data yang terkumpul didapatkan melalui observasi, interview, dan analisis dokumen yang dianalisa secara kualitatif berdasarkan form yang dikemukakan oleh Brown (2004). Hasil penilitian menunjukan bahwa retelling, role play, picture-cued story telling, discussion, picture-cued task, read aloud, and games merupakan teknik penilaian yang digunakan oleh guru. Practicality, efisiensi, dan authenticity merupakan alasan dibalik penggunaan teknik penilaian berbicara tersebut. Sedangkan, kesulitan dalam penerapan teknik penilaian tersebut adalah keterbatasan vocabulary yang dimiliki siswa, motivasi siswa, dan kemauan siswa untuk berbicara. Berdasarkan hasil penelitian, dapat disimpulkan bahwa berbagai macam teknik penilaian berbicara dapat digunakan dalam menilai kemampuan berbicara siswa. Untuk lebih lanjut, penting bagi guru untuk mengenali kesulitan siswa untuk memilih teknik penilaian yang tepat.